Analisis Usaha Penangkar Pembibitan Kelapa Sawit di Inkubator Agribisnis Fakultas Pertanian Universitas Riau - Zurika, Yandri; Hadi, Syaiful; Tarumun, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research have purposes to know the technical condition of oil palm seedlings in the Incubator Tenant In Wall Agribusiness Faculity of Agriculture Riau University and analyze income, and farm efficiency, the research is done at Incubator Agribusiness Agriculture Faculity Riau University. Sample is the descriptive qualitative and the analysist of farming Return Cost Ratio (RCR). The results of the research indicate that the condition of effort technical seedling the kinds of the palm breeding, topaz varietas, marihat varietas, and sain varietas by tenant in wall. Under categorized well and give aduantages and efficient. Â  Keywords : Analysis of Farming , Nursery Palm Oil , RCR . Tenant In Wall